O conhecimento ecológico local e a percepção ambiental de uma população de pescadores do Rio Grande do Sul - Baptista, Cristina Paes Barreto (Universidade do Vale do Rio dos Sinos, 2012)
The Knowledge of Traditional population can be an important tool in conservationist actions. Artisanal fishermen have a distinct knowledge about their surrounding environment. This thesis has as object 1) To identify the environmental perception of the fishermen as well as how age, fishing experience and time spent in school influence that perception 2) Identify the use of the wetlands and its fishing and water resources by a population of fishermen from the cities of Imbé and Tramandaí and 3) Investigate how the LEK(local ecological knowledge) can help elaborate management plans and if this knowledge is present on management plans and/or Conservation Unit's consultative councils in the Rio Grande do Sul state and co-management actions. The fishermen have a positive perception about their environment and there is no relation between negative perceptions regarding conservationist actions and social-economical factors. In this interaction between the fishermen from Tramandaí and Imbé with their surrounding ecosystem it was found a rich knowledge about that environment. Besides, much of that knowledge is in accordance to what is registered by the scientific community. The experience and lifestyle of the fishermen contribute positively to their preservationist view regarding the environment, making them strong allies in management plans, although their contribution is not well recongnized.
Keywords: Conservação da natureza; Pescadores; Proteção ambiental; Ecologia humana; Pescadores artesanais; Ecologia; Áreas úmidas; Tramandaí; ACCNPQ::Ciências Biológicas::Biologia Geral